Bending performance of SFCBs reinforced UHPC beams prestressed with FRP bars - Wenjie Ge; Feng Zhang; Subedi Sushant; Ashraf Ashour; Kangbao Chen; Shihu Fu; Linfeng Qiu; Laiyong Luo; Dafu Cao (Case Studies in Construction Materials)
This study investigates the bending performance of ultra-high-performance concrete (UHPC) beams reinforced with non-prestressed steel-FRP composite bars (SFCBs) and prestressed fiber-reinforced polymer (FRP) bars. The finite element software ABAQUS is used to simulate the strain behaviors of materials, applying a real strain model for concrete and equivalent plastic strain models for reinforcements. Six beams with different concrete types and reinforcements (prestressed or non-prestressed) are simulated and analyzed. These simulations yielded results that closely aligned with the results tested. Based on the validated FE models, a parametric analysis is conducted to examine the effects of mechanical properties of concrete, mechanical property of non-prestressed reinforcement, and the reinforcement ratio of prestressed FRP bars and non-prestressed SFCB on the bending performance of SFCBs reinforced UHPC beams prestressed with FRP bars. The results indicate that, as the concrete strength increases from C35 to UHPC140, both the ultimate load and ultimate deflection of flexural beams exhibit a gradual increase. Notably, employing UHPC100 as the matrix results in specimens achieving the highest ductility, deformation, and energy absorption. When non-prestressed FRP bars are replaced by SFCBs, the ultimate load of the beams decreases by 8 %, but energy absorption increases by 34 %. With an increase in the steel ratio of SFCBs, the ductility, deformation, and energy absorption also gradually increase. Moreover, increasing the reinforcement ratio of both prestressed FRP and non-prestressed SFCBs results in an increase in ultimate load, but a decrease in ultimate deflection, ductility, deformation, and energy absorption capacity. Additionally, by analyzing the comprehensive performance of various beams, the economic benefits of UHPC beams reinforced with non-prestressed SFCBs and prestressed FRP bars are less prominent, but they are still suitable for structures that require high strength, durability, and ductility. This research can provide valuable technical references for the analysis and design of UHPC beams reinforced with SFCBs and prestressed FRP bars.